Ion exchange membrane electrodialysis for water and wastewater processing: Application of ladder-type membrane spacers to impact solution concentration and flow dynamics - Al‑Amshawee, Sajjad Khudhur Abbas; Mohd Yusri, Mohd Yunus; Dakhil, Ihsan Habib (SPRINGER HEIDELBERG, 2025)
Concentration polarization, which creates a thin boundary layer along the membranes in electrochemical reactors and electrodialysis-related processes, is one of the main issues. Membrane spacers provide swirling motion in the stream and distribute fuid toward the membrane, which efectively breaks the polarization layer and maximizes fux steadily. Membrane spacers and the spacer-bulk attack angle are reviewed systematically in the current study. The study then in-depth reviews a ladder-type confguration composed of longitudinal (0° attack angle) and transverse (90° attack angle) flaments, and its efects on solution fow direction and hydrodynamics. The review discovered that, at the tradeof of high-pressure losses, a laddered spacer can provide mass transfer and mixing activity along the channel while preserving comparable patterns of concentration near the membrane wall. Pressure losses are driven by a change in the direction of velocity vectors. Dead spots in the spacer design that are created by the large contribution of the spacer manifolds can be reduced using the high-pressure drop. Laddered spacers also permit long, tortuous fow paths, which help to create turbulent fow and prevent concentration polarization. The absence of spacers produces limited mixing and broad polarization efects. A major portion of streamlines changes direction at ladder spacer strands positioned transverse to the main fow by moving in a zigzag manner up and down the flaments of the spacer. Flow at 90° is perpendicular to the transverse wires in x-coordinate, no change in y-coordinate.